2018
DOI: 10.1007/s10792-018-0828-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of dry eye symptoms on vision-related quality of life after phacoemulsification surgery

Abstract: Purpose To observe the long-term changes in dry eye symptoms and vision-related quality of life in agerelated cataract patients after phacoemulsification. Methods A total of 101 cataract patients after phacoemulsification combined with IOL implantation (Ph-IOL) in one eye were enrolled. Visual acuity, tear film breakup time (BUT), and Schirmer test 1 (ST1) were measured before and 1, 3, and 6 months after surgery. Ocular Surface Disease Index (OSDI) scores were used to evaluate the severity of dry eye symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
4
15
0
7
Order By: Relevance
“…A recent report by DEWS recommends non-invasive diagnostic tests [19]. Nevertheless, TBUT, together with the OSDI scores and Schirmer I test, is still the most commonly used parameter to ascertain the presence of DED and monitor its changes over time [20,21]. Our study population undergoing cataract surgery had similar features to that of previous studies [20,21].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A recent report by DEWS recommends non-invasive diagnostic tests [19]. Nevertheless, TBUT, together with the OSDI scores and Schirmer I test, is still the most commonly used parameter to ascertain the presence of DED and monitor its changes over time [20,21]. Our study population undergoing cataract surgery had similar features to that of previous studies [20,21].…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, TBUT, together with the OSDI scores and Schirmer I test, is still the most commonly used parameter to ascertain the presence of DED and monitor its changes over time [20,21]. Our study population undergoing cataract surgery had similar features to that of previous studies [20,21]. Of the whole study population, individuals with normal ocular surfaces (TBUT [ 7 s) and no relevant DED symptoms (OSDI B 12) were just 38% at baseline.…”
Section: Discussionmentioning
confidence: 85%
“…Tear film instability and inappropriate quality is known to adversely affect image quality [ 45 , 46 ]. Xue et al found that vision-related quality of life negatively correlates with dry eye symptoms and positively correlates with visual acuity after phacoemulsification [ 47 ]. The tear film has a high impact on optical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Dry eye symptoms and signs were evaluated at postoperative 1 week and 1 month, however previous studies have shown that dry eye syndrome significantly deteriorated for 1 month after surgery and gradually improved over 6 months. We consider that evaluation for a longer follow-up period may yield more accurate results [33]. In addition, the evaluation of dry eye symptoms and signs according to presence or absence of preoperative dry eye syndrome could be assessed by further studies.…”
Section: Discussionmentioning
confidence: 99%